PENILAIAN MAHASISWA TERHADAP TUTOR DALAM PENGUASAAN MATERI PEMBELAJARAN PADA DII PERPUSTAKAAN UPBJJ-UT BANJARMASIN - Amani, Mukhyar; Suci Anita, Andi (Vidya Karya Jurnal Kependidikan, 2015)
The Open University is a higher education institute which applies a long distance learning system requiring the university students to learn independently. But, due to various factors, among others, their habit of depending on the information directly presented by the teacher, the majority of the university students have not yet been able to learn independently. One of the methods that can be used to cope with this problem is the tutorial learning pattern. Tutorial is one of the forms of service and learning guidance given to the university students in order to help them to achieve an optimal learning result through face-to-face tutorial, written tutorial, internet tutorial, radio tutorial, and computer-aided tutorial.Â  The tutorial process is guided by a tutor playing the roles of facilitator and motivator. The performance of a tutor affects the tutorial results very much. Based on the research result, it was known that the performance of the tutors of UPBJJ-UT Banjarmasin in 4 learning groups (pokjar) â namely those in the regencies of Tapin, Hulu Sungai Selatan, Hulu Sungai Utara, and Tabalong â toward the mastery of the materials had obtained the average score of 3.14 in the Good category.